TRANSFORMATION OF THE ROLE OF CHINA IN THE AFGHAN ISSUE AND ENSURING SECURITY IN CENTRAL ASIA - G. A. Sizov (Сравнительная политика)
Peace in Central Asia (CA) and Afghanistan directly affects China's long-term economic and security interests. In particular, it concerns ensuring stability in the Xinjiang Uygur Autonomous Region (XUAR) and promoting the Chinese Silk Road Economic Belt. That is why cooperation with Central Asian states in this area remains significant for Beijing. Since 2014, a certain militarization of Beijing’s approach to ensuring the security of its own interests abroad has been taking place, which is especially noticeable in Afghanistan. However, here too, China’s policy is more protective in nature and often lies in the “gray zone”, as statements by official authorities and various media reports create a dual impression of the presence of a Chinese military presence in the Afghan border area. Despite stepping up diplomatic efforts and expanding the military component of its policy, China’s influence on the Afghan peace process remains limited and is primarily aimed at containing threats to its interests in the XUAR and Central Asia.